Heme Cytotoxicity and the Pathogenesis of Immune-Mediated Inflammatory Diseases - Larsen, Rasmus; Gouveia, Zélia; Soares, Miguel P.; Gozzelino, Raffaella (Frontiers in Pharmacology, 2012)
Heme, iron (Fe) protoporphyrin IX, functions as a prosthetic group in a range of hemoproteins essential to support life under aerobic conditions. The Fe contained within the prosthetic heme groups of these hemoproteins can catalyze the production of cytotoxic reactive oxygen species (ROS). Presumably for this reason, heme must be sequestered within those hemoproteins, thereby shielding the reactivity of its Fe-heme. However, under pathologic conditions associated with oxidative stress, some hemoproteins can release their prosthetic heme groups. While this heme is not necessarily damaging per se, it becomes highly cytotoxic in the presence of a range of inflammatory mediators such as tumor necrosis factor (TNF). This can lead to tissue damage and, as such, exacerbate the pathologic outcome of several immune mediated inflammatory conditions. Presumably, targeting “free heme” may be used as a therapeutic intervention against these diseases.